Decreased risk of COVID-19 pneumonia in children and adolescents during the Delta variant emergence. (March 2022) - Murillo-Zamora, E.; Trujillo, X.; Huerta, M.; Ríos-Silva, M.; Baltazar-Rodríguez, L.M.; Guzmán-Esquivel, J.; Benites-Godínez, V.; Ortega-Ramírez, A.D.; Mendoza-Cano, O.
Abstract: Objectives: This study aimed to evaluate factors associated with the risk of COVID-19 pneumonia in children (aged <10 years) and adolescents (aged 10–19 years) before (March 2020–April 2021) and during (May–July 2021) the Delta (B.1.617.2) variant emergence. Study design: A retrospective and nationwide cohort study was conducted in Mexico. Methods: Data from 26, 961 laboratory-confirmed cases of COVID-19 were analyzed. Risk ratios (RRs) and 95% confidence intervals (CIs) were used to evaluate the association of the evaluated exposures with the risk of COVID-19 pneumonia. Results: The overall incidence rate of pneumonia was 23.0 per 10, 000 person-days, and it was lower during the Delta variant emergence (30.3 vs. 9.4 person-days, p < 0.001). In multiple analysis, a decreased risk of pneumonia was observed among those cases occurring in May 2021 or later (vs. March 2020–April 2021, RR = 0.98, 95% CI 0.97–0.99) and among older patients (RR per year = 0.998, 95% CI 0.996–0.998). Other comorbidities (namely, obesity, chronic kidney disease, diabetes mellitus, immunosuppression, or malignant tumors) were associated with an increased risk of severe COVID-19 manifestations. Conclusions: Our findings suggest that during the Delta variant emergence, children and adolescent patients were at reduced risk of COVID-19 pneumonia in Mexico. Further research is needed to identify factors determining the observed scenario.